2017
DOI: 10.1007/s00204-017-2061-3
|View full text |Cite
|
Sign up to set email alerts
|

Early life arsenic exposure, infant and child growth, and morbidity: a systematic review

Abstract: Epidemiological studies have suggested a negative association between early life arsenic exposure and fetal size at birth, and subsequently with child morbidity and growth. However, our understanding of the relationship between arsenic exposure and morbidity and growth is limited. This paper aims to systematically review original human studies with an analytical epidemiological study design that have assessed arsenic exposure in fetal life or early childhood and evaluated the association with one or several of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 38 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Further studies are needed to understand the impact of heavy metal exposure on bacterial virulence properties. Several studies have reported a higher incidence of diarrheal diseases among children in arsenic-endemic areas [ 33 , 57 59 ]. However, whether it is due to the higher prevalence of diarrheal pathogens in the area or due to the vulnerability of the population to diarrhea with respect to their arsenic exposures, hygiene, sanitation, or access to clean drinking water supply is not well explained.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to understand the impact of heavy metal exposure on bacterial virulence properties. Several studies have reported a higher incidence of diarrheal diseases among children in arsenic-endemic areas [ 33 , 57 59 ]. However, whether it is due to the higher prevalence of diarrheal pathogens in the area or due to the vulnerability of the population to diarrhea with respect to their arsenic exposures, hygiene, sanitation, or access to clean drinking water supply is not well explained.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that with chronic As exposure, LL-37 levels may remain elevated in the systemic circulation owing to its role in innate immune surveillance and chemoattractant activity. Elevated LL-37 levels, in turn, may promote inflammation and have long-lasting consequences for decreased lung function (Jiang et al 2012) or chronic lung disease later in life (Sanchez et al 2016;Rahman et al 2017). The stimulating effects of As exposure on LL-37 levels may be masked by multiple stress factors in growth-retarded children, thus hindering the optimum response.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown increased risk of morbidity in children, particularly related to respiratory tract infections (RTI) and diarrheal diseases, due to chronic and early life arsenic (As) exposure (Raqib et al 2009;Sanchez et al 2016;Rahman et al 2017). Emerging evidence indicates that As has multiple harmful effects on immune regulation and its surveil-lance system which potentially amplify susceptibility to many infectious diseases as well as other immune-related health outcomes (Ferrario et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More recent epidemiological studies have shown increased risks for children to arsenic in water for outcomes such as respiratory disease following in utero early life exposures, diarrhea, diabetes, increased risks of infections, and adverse developmental outcomes [ 14 ]. For example in a systematic review of studies that met the criteria for conducting an analytical epidemiological study (i.e., biological monitoring in relation to disease outcome), findings consistently linked higher arsenic levels to higher rates of respiratory infections and diarrhea in children [ 20 ]. In a study conducted in Bangladesh for 200 children, strong associations were also found between higher levels of arsenic in well water and urine and lower intellectual function [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to heavy metals, such as arsenic, has also been implicated in the development of autism spectrum disorder in a study of 364 children [ 22 ]; however more confirmative studies are needed to look at mechanisms of action. Oxidative stress mechanisms, requiring further research, are believed to be one manner in which arsenic causes damage [ 20 ]. Genetic polymorphisms may also contribute to how both adults and children biologically respond to arsenic exposures [ 4 ].…”
Section: Introductionmentioning
confidence: 99%